Instrumento, processo, estratégia: Caldas do Moledo como laboratório metodológico da metamorfose do Lugar e do Tempo nas paisagens arquitectónicas do Douro - Ana Filipa Moreira Dias (2018)
The present work thrives from the desire to participate in the revision of contemporarymethods of seeing, thinking and intervening in 'architectural landscapes'. Through the proposalof an 'Instrument', 'Process' and 'Strategy' it is hoped to contribute to the construction of currenturban realities, having Douro and Caldas do Moledo as a methodological laboratory of thesepremises.Caldas do Moledo, known as the entrance gate to the heart of the Douro thanks to itsstrategic position on the right bank of the river, has always been of great importance in the culturalexchange of this region. In spite of the marked predominance of the vineyard's monoculture, thecase study presents pluralities and diversities along its extent, constituting an urban set greatlydue to the action of one of the most outstanding personalities of the Douro, 'Ferreirinha'. Newcentralities and systems emerge in the region, and places like Caldas do Moledo, once a featurein the landscape, now a memory of other times, are suspended in time. The construction of astrategy for Caldas do Moledo seeks to understand and articulate the possibilities of recoveringa place full of character, history and heritage values that, although constrainded by the abandonment and the passage of time, holds potentialities within the contemporary dynamics, both locallyand regionally. It will be presented a vision, not only territorial and architectural, but also social,economic and cultural, which does not identify with the relations and superficial images of theDouro's tourism, seeking, instead, to value different qualities and atmospheres, or the GeniusLoci, of this and other places.Considering the transformation processes that the Douro region faces and through awork method based on the physical and formal analysis of the different dynamics, an attempt willbe made to highlight the fundamental principles of action that arise from the perception of thevalues and identities of this territory. Intervening in a place like Caldas do Moledo requires a reflection on the various identities, systems and dynamics present in this territory, be they historical,architectural, urban, economic, cultural or social.It is essential to undersand to carefully preserve and transform the material and immaterial heritage of the Douro Region, focused here in Caldas do Moledo, as much as it is imperativeto reconstruct a discourse that joins tradition and progress, truly representative of a 'Cultural,Evolving and Living Landscape '.